Assessment of acculturation in minority health research. (March 2017) - Fox, Molly; Thayer, Zaneta; Wadhwa, Pathik D.
Abstract: Acculturation represents an important construct in the context of health disparities. Although several studies have reported relationships between various aspects of acculturation and health in minority populations, crucial inconsistencies remain. One likely reason for these inconsistencies may relate to limitations in the conceptualization and operationalization of acculturation, particularly in the context of health research. The acculturation construct underwent major conceptual and operational change when it was adapted from anthropology to psychology, and we argue another major shift is now required for use of this construct in health research. Issues include determining whether acculturation measures should focus on an individual's internal attitudes or overt behaviors; whether they should characterize cultural orientation status at a given point in time or change over time; whether measures should be culture-specific or more global in nature; how the issue of multiculturalism should be addressed; how measures can optimally incorporate multiple dimensions of acculturation; and whether proxy measures should be used. These issues are important in the context of health research because of their implications for determining the direct and indirect effects of cultural change on health-related biological and behavioral processes. We elaborate on and address each of these issues from a perspective that spans multiple disciplines across the biological and social sciences, and offer concrete recommendations with the ultimate goal of achieving a better understanding of the role of acculturation in minority health and health disparities. Highlights: Acculturation has been inadequately conceptualized and measured for health research. Acculturation can have direct and indirect effects on biology and behavior. Personal identity, values, behavior and cultural change affect biology differently. Proxies of acculturation (e.g. nativity) can generate spurious correlations with health. Statistical methods should reflect the multi-dimensional aspects of acculturation.